1992
DOI: 10.1002/jcc.540130203
|View full text |Cite
|
Sign up to set email alerts
|

On the numerical solution of the multidimensional vibrational time‐independent Schroedinger equation

Abstract: A preliminary study of the capability of the finite difference and finite element methods (FDM, FEM) to evaluate eigenvalues of one-, two-, and three-dimensional self-adjoint operators is reported with reference to applications dealing with the description of vibrational levels. Results of harmonic oscillator model potentials and ab initio PES for the water molecule are obtained by using the FDM. In spite of the large matrices used, low accuracy, nonvariational results are found. A different method, based on F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…Our results are shown in Table 1 along with previous results calculated by FDM [60] and FEM [61] methods. The element volumes are specified by the shape type and number of nodes; for example, HEX27 is a hexahedral basis function with 27 nodes.…”
Section: Resultssupporting
confidence: 49%
“…Our results are shown in Table 1 along with previous results calculated by FDM [60] and FEM [61] methods. The element volumes are specified by the shape type and number of nodes; for example, HEX27 is a hexahedral basis function with 27 nodes.…”
Section: Resultssupporting
confidence: 49%
“…I͒ a pure stretching 1D harmonic model is a very poor representation of the kinetic energy operator T d , since large 3D movements of the H d nucleus are involved. An internal coordinate [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] 3D model seems to be a better representation of T d .…”
Section: The Kinetic Energy Operatormentioning
confidence: 99%
“…Also, it may be observed that the distances R ab , R ac , and R ad are maintained to first order and that the two bending movements become equivalent when h ϭ0, the triatomic case. 45 The Jacobian matrix J r ͓Eq. ͑4͔͒ can be easily obtained from Eqs.…”
Section: ͑13͒mentioning
confidence: 99%